Recursos educativos digitales del portal Educar Ecuador para apoyar a los docentes del subnivel medio de la Escuela de Educación Básica Ciudad Ibarra, Zamora Chinchipe, año lectivo 2021-2022 - Ortega Medina, Maria Alexandra (2023)
The Ecuadorian Ministry of Education gives openness to technology and innovation, give teachers digital educational resources through Educar Ecuador portal of easy access and use, which allow to include in their didactic plan quickly, strengthening the teaching-learning process with a more interactive environment. Therefore, the main objective of this research was to define the digital educational resources of the Educar Ecuador portal that support the teachers of the intermediate level of the Basic Education School "Ciudad Ibarra" of Zamora Chinchipe province, school year 2021-2022; through a descriptive-exploratory scope, being of deductive-inductive method with a quantitative approach; with the checklist technique, with a specific population of 15 resources. For this purpose, an analysis was made of the learning objects review instrument (LORI) and it was adapted by dimensions and criteria established by the National Institute of Educational Technologies and Teacher Training, which contains different quality indicators that specify the characteristics to measure the relevance of educational resources so that they meet the objectives requested by the current curriculum, thus through the application of the adapted instrument it was obtained that 11 resources meet the criteria, from the value 86.17% to 96.88%; while 4 resources partially comply that reach a score of 72.77% to 83.49%, these resources enter in the classification where the main characteristics are detailed, allowing to choose the appropriate resource according to their needs, bearing in mind the indicators that show a score less than one (1), in this case the teachers at the time of implementing in their planning is according to their experience and according to the evaluated criteria. Key words: Digital educational resources, Educar Ecuador portal, Instrument LORI, Evaluation dimension.